Gravitropism interferes with hydrotropism via counteracting auxin dynamics in cucumber roots: clinorotation and spaceflight experiments. Issue 4 (19th July 2017) - Morohashi, Keita; Okamoto, Miki; Yamazaki, Chiaki; Fujii, Nobuharu; Miyazawa, Yutaka; Kamada, Motoshi; Kasahara, Haruo; Osada, Ikuko; Shimazu, Toru; Fusejima, Yasuo; Higashibata, Akira; Yamazaki, Takashi; et al.
Summary: Roots of land plants show gravitropism and hydrotropism in response to gravity and moisture gradients, respectively, for controlling their growth orientation. Gravitropism interferes with hydrotropism, although the mechanistic aspects are poorly understood. Here, we differentiated hydrotropism from gravitropism in cucumber roots by conducting clinorotation and spaceflight experiments. We also compared mechanisms regulating hydrotropism and auxin‐regulated gravitropism. Clinorotated or microgravity (μG)‐grown cucumber seedling roots hydrotropically bent toward wet substrate in the presence of moisture gradients, but they grew straight in the direction of normal gravitational force at the Earth's surface (1G) on the ground or centrifuge‐generated 1G in space. The roots appeared to become hydrotropically more sensitive to moisture gradients under μG conditions in space. Auxin transport inhibitors significantly reduced the hydrotropic response of clinorotated seedling roots. The auxin efflux protein CsPIN5 was differentially expressed in roots of both clinorotated and μG‐grown seedlings; with higher expression in the high‐humidity (concave) side than the low‐humidity (convex) side of hydrotropically responding roots. Our results suggest that roots become hydrotropically sensitive in μG, and CsPIN5‐mediated auxin transport has an important role in inducing root hydrotropism. Thus, hydrotropic and gravitropic responses in cucumber roots may compete via differential auxin dynamics established in response to moisture gradients and gravity.